Faktor risiko tingkah laku relaps dadah dalam kalangan pelatih wanita di Cure and Care Rehabilitation Centre (CCRC) - Norruzeyati Che Mohd Nasir; Mohammad Rahim Kamaluddin; Mohd Alif Jasni (Penerbit Universiti Kebangsaan Malaysia, 2020)
The issue of drug addiction among women has shown a significant increased over the years. One of the issues related to drug addiction is drug relapse. Most studies on drug addiction focus on male clients and thus contribute to intervention strategies that appropriate for male. An effective intervention strategy must be client-based as well as gender-based intervention. Therefore, this study is aimed to explore the risks factors of drug relapse involving female clients in Cure and Care Rehabilitation Centre (CCRC) Bachok, Kelantan. This study utilized qualitative research design, consisted of an in-depth interview with 11 informants, who are chosen based on the purposive sampling technique. The data obtained from the interview were analyzed using thematic analysis through Nvivo 10 software. There are three main themes emerged that explain the risk factors of drug relapse among women; employment issues, internal factors or emotional strain and push and pull factors from the informant's social system. This study proposes that intervention strategies should be holistic and integrative by incorporating a client’s ecological systems, namely micro, mezzo and macro levels. Emphasis should also be given to the client's psychological aspects.